2011
DOI: 10.4304/tpls.1.9.1222-1226
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Memory Strategy Instruction on Learners' EFL Vocabulary Retention

Abstract: Abstract-The Depth of Processing Hypothesis (DPH) suggests that the more cognitively one is engaged in learning a word, the more likely it is to remember it later. This study was an attempt to test and substantiate this Hypothesis by assessing the impact of memory strategy instruction on learners' short-term and long-term vocabulary retention. True experimental design was employed to study two classes of 40 randomly selected intermediate learners as control and experimental groups. Both groups were exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…The results also show an outstanding performance in students' knowledge base of the examined items after both strategies are assigned in the classrooms under investigation, and this is noticed in the mean values of both groups at the end of the experiment (M = 11 & 8.33) for both the experimental group and the control group respectively. This leads to the conclusion that both semantic mapping and rote memorization can be used in the classroom setting to boost students' acquisition of second language vocabulary in agreement with other studies (e.g., Ghorbani & Riabi, 2011;Khoii & Sharififar, 2013;Nilforoushan, 2012;Radwan & Rikala-Boyer, 2011), in which both strategies are effective to enlarge students' knowledge of L2 vocabulary if used in the classroom context.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results also show an outstanding performance in students' knowledge base of the examined items after both strategies are assigned in the classrooms under investigation, and this is noticed in the mean values of both groups at the end of the experiment (M = 11 & 8.33) for both the experimental group and the control group respectively. This leads to the conclusion that both semantic mapping and rote memorization can be used in the classroom setting to boost students' acquisition of second language vocabulary in agreement with other studies (e.g., Ghorbani & Riabi, 2011;Khoii & Sharififar, 2013;Nilforoushan, 2012;Radwan & Rikala-Boyer, 2011), in which both strategies are effective to enlarge students' knowledge of L2 vocabulary if used in the classroom context.…”
Section: Discussionsupporting
confidence: 88%
“…The effectiveness of memory strategies on students' retention of words has been the topic of many previous studies (e.g., Abbasi, Hassaskhah, & Tahriri, 2018;Ghorbani & Riabi, 2011;Nemati, 2013;Sagarra & Alba, 2006). The results from these studies showed the significant impact of memory strategies on students' retention of words on the basis that these strategies succeeded in activating the human mind to conduct high level of word processing.…”
Section: Related Studiesmentioning
confidence: 97%
“…In other words, it would make the learners able to retrieve new information. Some other researchers also supported the idea of using memory strategy for vocabulary learning are Zoghi and Maleki (2015), Ghorbani and Riabi (2011) who gave superiority to keyword method and others such as Borza and Gorjian (2015), Zahedi and Abdi (2012) who supported the significant role of semantic mapping. All of the mentioned studies tried to prove the effects of VLS on the vocabulary learning; however, the question of what strategy is the most influential yet remains an issue that requires more research be done.…”
Section: Memory Strategy and Vocabulary Retentionmentioning
confidence: 92%
“…This was also similar to the responses of Adel-1 and Adel-2 who mentioned that they actually make it a habit to read every time they had an English language lesson in school. This helps their retentive memory (Ghorbani & Riabi, 2011).…”
Section: Responses Of 2 Nd Category Of Respondentsmentioning
confidence: 99%